Spiritual meal, identity and community in Bohemia 1400-1650: historical anthropology and the reformation of religious food and textual practices - Capska, Veronika; Čapský, Martin (Routledge, 2024)
The article explores the early Bohemian reformation (Utraquism) as an alternative Central European project of church reform that has not been as closely connected with the Western European civilizational narrative as the Lutheran reformation. The authors build on cultural anthropological approaches and on the recent 'material turn'. They draw attention to the close historical associations between holy food and holy texts and look into the reformation of religious food and textual practices. They explore how the chalice functioned as a symbol of inclusivity and collective identity and how this became manifest in material culture. The authors analyse innovations in chalice shape (lips and tubes) and provide evidence of private or family chalices, arguing that such chalices re-introduced elements of social hierarchy in the Utraquist communion. In relation to holy food, the authors also focus on fasting, distinguishing two main lines of discourse: 1) the continuation of the medieval religious discourse of gluttony; and 2) difficulties connected with observing fasting regulations north of the Alps. Finally, they point out that the Bohemian reformation lends itself to a study of changing symbols, as suggested by Peter Burke, and they explore the model-like process through which book(s) largely replaced chalice(s) as the main symbol(s) and source(s) of identity among reformed non-Catholic Christians in the new religious situation in Bohemia after 1620.
Duchovní pokrm, identity a komunita v Čechách 1400-1650: Historická antropologie a reformace náboženských stravovacích a textových praxí
Keywords: Historical anthropology; reformation(s); new material culture history; communities; Utraquists; Eucharist; Historická antropologie; reformace; dějiny nové hmotné kultury; komunity; utrakvisté; eucharistie